The main biomechanical risk factors for the prevalence of the left hip joint traumatic and degenerative changes - Lovrić, Ivan, liječnik (Array, 2009)
Abstract: The aim of this paper is to examine characteristic biomechanical features leading to the acetabular fracture and hip joint arthrosis, and to explain the prevalence of the left side traumatic and degenerative pelvic pathology that is usually seen in diverse groups of patients. A total of 253 patients were analyzed in a retrospective case-control study during a six-year period. The patients were divided into the case group of 103 patients suffering traumatic acetabular fractures and into the control group of 150 patients with hip joint arthrosis, where operative aloarthroplasty was not yet performed. The data of the affected hip joint range of motions in the case and control group of patients were statistically analyzed correlating the difference in frequency of the left and right hip joint pathology. The left acetabulum was affected more commonly in both groups of patients, while arthrosis of the left hip joint was more commonly recorded in the control group. More frequent pathology of the left hip joint, found in both groups of patients, was probably due to weaker neuromuscular function of the left pelvic side, which was also more exposed to injury due to the greater input of forces to the left hip joint during a traffic accident